2022
DOI: 10.3390/beverages8020025
|View full text |Cite
|
Sign up to set email alerts
|

The Healthy Eater’s Idea and Related Behavior of a Healthy Diet—A Case Study with Kombucha Drinkers

Abstract: Consumers’ demand for ‘healthy’ food is growing at a fast pace. Beverages are one of the fastest-growing segments in the healthy food market. Kombucha is a product with a rapid market growth and is considered a ‘healthy beverage’. Kombucha drinkers (n = 296) in the contiguous United States (U.S.) were targeted to investigate differences in the various consumer segments regarding the healthy eater’s behavior, namely—(1) healthy diet stage-of-change attitudes, (2) healthy eating criteria, and (3) label informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…In the case of vitamin D-enriched juices, most of the participants were in the pre-contemplation stage and they had no intention for consuming this drink. Most of the participants had regular consumption of probiotic drinks (maintenance stage), which was consistent with the study of Kim Juyoung et al (31)in relation to a probiotic and functional drink.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the case of vitamin D-enriched juices, most of the participants were in the pre-contemplation stage and they had no intention for consuming this drink. Most of the participants had regular consumption of probiotic drinks (maintenance stage), which was consistent with the study of Kim Juyoung et al (31)in relation to a probiotic and functional drink.…”
Section: Discussionsupporting
confidence: 89%
“…They concluded that it was not possible to distinguish how education level and socio-economic characteristics clearly affect the consumption of functional foods (3). However, in the results of other studies, these demographic variables were signi cantly different, such as the study of Kim,Juyoung et al (31)in which the effect of gender, education, geographic region and culture were signi cant.…”
Section: Demographic Informationmentioning
confidence: 80%
“…However, in the results of other studies, these demographic variables were significantly different, such as the study of Kim et al . 37 in which the effect of gender, education, geographic region and culture were significant.…”
Section: Discussionmentioning
confidence: 94%
“…Most of the participants had regular consumption of probiotic drinks (maintenance stage), which was consistent with the study of Kim et al . 37 in relation to a probiotic and functional drink.…”
Section: Discussionmentioning
confidence: 99%
“…The detection of erythritol only in hard kombucha samples in our survey, on the other hand, is less readily explainable. As a noncaloric sweetener, erythritol addition likely reflects attempts to appeal to health-conscious consumers [2,36]. Alternatively, hard kombucha producers may be taking advantage of the relative microbial stability conferred by ethanol, acidity, and low residual sugars and therefore using erythritol for organoleptic balance without a risk of continued in-package fermentation, even when stored at non-refrigeration temperatures.…”
Section: Discussionmentioning
confidence: 99%